2014
DOI: 10.1123/pes.2013-0120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Modes and Frequency of Commuting to School in Youngsters: A Systematic Review

Abstract: The first objective was to review and analyze self-reported measures used for assessing mode and frequency of commuting to and from school in youngsters (4-18.5 years old). The secondary objective was to conduct a qualitative appraisal of the identified studies. We searched five online databases: PubMed, SportDiscus, ProQuest, National Transportation Library, and Web of Knowledge. Four categories of search terms were identified: self-report, active transportation, school-aged children and school. Titles and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 0 publications
2
58
1
11
Order By: Relevance
“…The outlined process for merging ACS data from multiple studies may help researchers, health promoters, transport planners and policy makers in their efforts to combine data related to mode of commuting to/from school from multiple sources of data. We previously reported the high heterogeneity in self-report questionnaires in studies assessing the mode of commuting to/from school conducted to date (40). This article provides a potential solution to standardize these diverse measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The outlined process for merging ACS data from multiple studies may help researchers, health promoters, transport planners and policy makers in their efforts to combine data related to mode of commuting to/from school from multiple sources of data. We previously reported the high heterogeneity in self-report questionnaires in studies assessing the mode of commuting to/from school conducted to date (40). This article provides a potential solution to standardize these diverse measurements.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, age, income and the number of perceived barriers are with less active community in both high and low-to-middle income countries 9 . However, the evidence on the barriers to active commuting in adolescents is just beginning to emerge and only few studies have been conducted in low and middle-income countries, specifically in the Latin America region 10 . In fact, to this date only three studies have been conducted in Latin America [11][12][13] and found that active commuting to school was associated with gender (boys), age (12-16 years old), place of residence (urban), travel time (<15 minutes) and family income (<R$1,000) 5,6 .…”
Section: Barriers For Active Commuting To Schoolmentioning
confidence: 99%
“…The questionnaire has been proposed as the most appropriate measurement for asking about mode of commuting to school after reviewing 158 studies within the scientific literature [10]. The questionnaire included sociodemographic data and a question about the frequency and mode of commuting: How did you commute to and from school the last week?.…”
Section: Methodsmentioning
confidence: 99%